(3GdCMcGe GdTQYjI GdcHQis - (3YHO GdMb Hf YHO GdQMef Hf YHO Gddg GdCROj GdETHjdj, CHh eMeO, GdeYQha H` GHf GdNQGW,J (B581 (3g` s
(3ChdgG (B:s
(3cJGH GdOjGJ hGdMOhO bSe Yf CHj HcQ Yf GdfHi Udi Gddg Ydjg hSde Cfg bGd Ef GdReGf cgjFJg jhe Ndb Gddg GdSehGJ hGdCQV s
(3BNQgG (B:s
(3aNQL GdfHi Udi Gddg Ydjg hSde hgh jbhd (B: (3GdMeO ddg GdPi CfbPg ef GdfGQ ced GdSaQ GdSGHY jJdhg ai GdKGef HGH ai GdWH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B92s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HGdQHGW (B(976) s
Keywords: (3Gdabg GdeGdcjs